New Insights on Biofilm Antimicrobial Strategies - Melo, Luís; Azevedo, Nuno F. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Over the last few decades, the study of microbial biofilms has been gaining interest among the scientific community. These microbial communities comprise cells adhered to surfaces that are surrounded by a self-produced exopolymeric matrix that protects biofilm cells against different external stresses. Biofilms can have a negative impact on different sectors within society, namely in agriculture, food industries, and veterinary and human health. As a consequence of their metabolic state and matrix protection, biofilm cells are very difficult to tackle with antibiotics or chemical disinfectants. Due to this problem, recent advances in the development of antibiotic alternatives or complementary strategies to prevent or control biofilms have been reported. This book includes different strategies to prevent biofilm formation or to control biofilm development and includes full research articles, reviews, a communication, and a perspective.